Respuesta :
Answer:
This is true.
Step-by-step explanation:
Step 1: see that √27 is the same as √3*3*3 and thus 3√3
Step 2: remove parenthesis so that 2(1-3√3) becomes 2 - 6√3
Step 3: observe that the equation now becomes 6√3 + 2 - 6√3 = 2
if you simplify any further, you are left with 0=0, which is true.
Comment if there is any step that requires more details...
[tex]6\sqrt{3}+2-2\sqrt{27} = 2[/tex]
[tex]6\sqrt{3}+2-2\sqrt{3\cdot 9} = 2[/tex]
[tex]6\sqrt{3}+2-2\cdot\sqrt{3}\cdot \sqrt{9}=2[/tex]
[tex]6\sqrt{3}+2-2\cdot \sqrt{3}\cdot 3=2[/tex]
[tex]6\sqrt{3}+2-6\sqrt{3}=2[/tex]
[tex]2=2[/tex]